Implementing the Family Talk Intervention among families with a severely ill parent or child with palliative care needs- a longitudinal study of the perspectives of hospital social workers - Thermaenius, Ingrid; Holm, Maja; Årestedt, Kristofer; Udo, Camilla; Alvariza, Anette; Lundberg, Tina; Wallin, Lars; Lövgren, Malin (Frontiers in Health Services, 2025)
BackgroundThe Family Talk Intervention (FTI) is a psychosocial intervention supporting families where a family member has palliative care needs. This study aimed to evaluate how the Family Talk Intervention (FTI) was implemented over time from the perspective of hospital social workers (HSWs) in their everyday clinical practice among families with a severely ill parent or child in need of palliative care.MethodsHSWs (n = 21) working in adult and children's care completed a 10-day education where they were trained to use FTI. The education was part of a multifaced implementation strategy involving educational outreach visits, facilitation, clinical implementation meetings, and audit and feedback. The HSWs were then expected to use FTI in their clinical practice to support families with dependent children. To assess if and how FTI was integrated into their daily practice, they were also asked to complete the Swedish version of the Normalization Process Theory Measure (S-NoMAD) on three occasions: on completion of the FTI-education, six months later, and one year later. For the longitudinal analysis of data, Friedman's test was used.ResultsThe HSWs rated the use of FTI high after completing the FTI-education, indicating a positive attitude towards FTI. In the longitudinal analysis, statistically significant changes were seen for two questions in S-NoMAD, where the HSWs' ratings showed that the FTI became more familiar and normalized over time. Generally, the HSWs' ratings of S-NoMAD's main constructs were high and stable over time, indicating a positive view of FTI and its implementation. However, for the single questions, the ratings were slightly more negative to some contextual aspects, such as managerial support and resources.ConclusionAs results showed, HSW mainly rated different aspects of the implementation process as positive, both from the beginning, but also over time. Therefore, the intervention could be judged to have been implemented as a tool to support families when a parent or a child is severely ill. Contextual factors, involving managerial support and resources were rated lower, indicating the importance of those aspects when introducing interventions into healthcare. The result also indicates that the multifaced implementation strategy supported the HSW's everyday clinical practice.Clinical Trial Registrationclinicaltrials, nr, identifier (NCT05365919; 2022-03-04 and; NCT05020158 2021-05-11).